2016
DOI: 10.1021/acs.inorgchem.6b00490
|View full text |Cite
|
Sign up to set email alerts
|

An Undecanuclear Ferrimagnetic Cu9Dy2 Single Molecule Magnet Achieved through Ligand Fine-Tuning

Abstract: ABSTRACT:We describe the concept of increasing the nuclearity of a previously reported high-spin Cu5Gd2 core using a "fine tuning" ligand approach. Thus two Cu9Ln2 coordination clusters, with Ln = Dy (1), Gd(2) were synthesized with the Gd compound having a ground spin state of 17/2 and the Dy analogue showing SMM behavior in zero field.In the burgeoning area of 3d-4f coordination clusters (CCs) for those showing Single Molecule Magnet (SMM) behavior it is becoming increasingly clear that the correct blend of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
24
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 19 publications
(25 citation statements)
references
References 31 publications
(74 reference statements)
1
24
0
Order By: Relevance
“…6H2O and the related Schiff base ligands with R = ethyl (L3), methyl (L2) or hydrogen (L1), see Scheme 2 and Table 1. Using the previously reported synthetic method for complex 1, 29 we observed that the combinations containing bromide ions lead to three completely different structures with the three ligands (1 to 3). On the other hand, we can see a clear trend when nitrate counter ions are available.…”
Section: Resultsmentioning
confidence: 93%
See 3 more Smart Citations
“…6H2O and the related Schiff base ligands with R = ethyl (L3), methyl (L2) or hydrogen (L1), see Scheme 2 and Table 1. Using the previously reported synthetic method for complex 1, 29 we observed that the combinations containing bromide ions lead to three completely different structures with the three ligands (1 to 3). On the other hand, we can see a clear trend when nitrate counter ions are available.…”
Section: Resultsmentioning
confidence: 93%
“…In this case, it seems that the differences in steric influence of the different ligands has no impact on the structure and a butterfly Cu2Dy2 compound (4 to 6) is always isolated. Complex 1, a Cu9Dy2 compound, was previously published, 29 but was the origin of this endeavor, and therefore will be mentioned in some parts of the following analysis. Scheme 2.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…While in one side, lanthanide ions (especially Dy III and Tb III ) possess Ising type anisotropy and large magnetic moment,, in the other side, 3d metal ions have the ability to participate in strong magnetic exchange interactions. Hence, in these complexes d‐f magnetic exchange can be utilized to increase the ground state spin multiplicity, thereby improving the SMM behavior . Moreover, it would be interesting to impart helical nature into these complexes for a variety of following reasons.…”
Section: Introductionmentioning
confidence: 99%